Nano-sized Mn2O3 prepared by a novel solvolysis route as an electrochemical capacitor electrode material - Ng, Kok Chiang; Cloke, Michael, Dr.; Prabaharanc, S. R. S., Assoc. Prof.; Chen, George Z., Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/